Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/pharmaceutics15071957
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Scaffolds as Microcarriers for Dynamic Culture of Human Neural Stem Cells

Abstract: Human neural stem cells (hNSCs) possess remarkable potential for regenerative medicine in the treatment of presently incurable diseases. However, a key challenge lies in producing sufficient quantities of hNSCs, which is necessary for effective treatment. Dynamic culture systems are recognized as a powerful approach to producing large quantities of hNSCs required, where microcarriers play a critical role in supporting cell expansion. Nevertheless, the currently available microcarriers have limitations, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…To ensure homogeneity and the removal of air bubbles, the solution was mixed again in the Thinky mixer. The resulting solution was cast into commercial tissue culture microplates, refrigerated at 4 °C for 1 h, at −5 °C for 20 min, at −20 °C for 1 h, and then anneal at −2 °C for 2 h, followed by lyophilization using a SP VirTis Genesis Pilot lyophilizer (SP Scientific, USA) . Prior to cell seeding, the chitosan scaffolds were sectioned into 400 μm slices and disinfected with 70 and 90% ethanol, followed by rinsing with PBS 3 times for 10 min each.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure homogeneity and the removal of air bubbles, the solution was mixed again in the Thinky mixer. The resulting solution was cast into commercial tissue culture microplates, refrigerated at 4 °C for 1 h, at −5 °C for 20 min, at −20 °C for 1 h, and then anneal at −2 °C for 2 h, followed by lyophilization using a SP VirTis Genesis Pilot lyophilizer (SP Scientific, USA) . Prior to cell seeding, the chitosan scaffolds were sectioned into 400 μm slices and disinfected with 70 and 90% ethanol, followed by rinsing with PBS 3 times for 10 min each.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have indicated that chitosan scaffolds with near-neutral charge enhance the adhesion and proliferation of human neural stem cells, outperforming negatively charged collagen scaffolds and chitosan−hyaluronic hybrid scaffolds. 39,40 Additionally, it has been reported that pure chitosan materials enhance the proliferation and pluripotency of hiPSCs. 31,41 Here, the zeta potential of our chitosan scaffolds showed minimal variation, maintaining nearneutrality despite changes in pH, which suggests a favorable setting for iPSCs attachment.…”
Section: Chitosan Scaffold Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These scaffolds can be classified into three types: natural scaffolds, synthetic scaffolds and hybrid scaffolds [ 98 ]. Natural scaffolds mainly include scaffolds made of natural biomaterials such as collagen [ 99 ], fibrin [ 100 , 101 ], gelatin [ 102 , 103 ], hyaluronic acid [ 104 ], chitosan [ 105 ], alginate [ 106 ], agarose [ 107 ], matrigel [ 108 ] and other biomaterials. On the other hand, synthetic scaffolds contain scaffolds synthesized from materials such as polyethylene glycol (PEG) [ 109 , 110 ], polyvinyl alcohol (PVA) [ 111 ], poly lactic-co-glycolic acid (PLGA) [ 112 , 113 ], polylactic acid (PLA) [ 114 ], polycaprolactone (PCL) [ 115 , 116 ] and others [ 70 ].…”
Section: D Cell Culturementioning
confidence: 99%
“…On the other hand, synthetic scaffolds contain scaffolds synthesized from materials such as polyethylene glycol (PEG) [ 109 , 110 ], polyvinyl alcohol (PVA) [ 111 ], poly lactic-co-glycolic acid (PLGA) [ 112 , 113 ], polylactic acid (PLA) [ 114 ], polycaprolactone (PCL) [ 115 , 116 ] and others [ 70 ]. Both natural and synthetic materials can be fabricated into porous scaffolds for 3D cell culture [ 105 , 112 ]. While natural scaffolds offer better biocompatibility, they may vary between batches or donors.…”
Section: D Cell Culturementioning
confidence: 99%